URINARY METABOLITES AS INDICATORS OF HUMAN EXPOSURE TO CHEMICAL CARCINOGENS - Radosavljevic, Vladan Radisa (HEALTH CARE, 2021)
Population exposure to environmental chemical carcinogens is a growing public health problem. Carcinogenic chemicals may be classified into two groups: genotoxic and non-genotoxic. A genotoxic chemical has a potential to induce the development of cancer, either in direct interaction with DNA or with cell structures, which are responsible for the maintenance of genome integrity. A non-genotoxic chemical has a potential to induce cancer indirectly by entering the processes of cancer etiopathogenesis. Previous research studies indicate that inorganic arsenic compounds may be associated with various malign diseases (lung cancer, urinary bladder cancer, skin, kidney, liver and prostate cancer). Inorganic arsenic is mainly present in meat, dairy products and grains, while organic arsenic (arsenobetaine) is present in seafood, fruit and vegetables. Benzene metabolites are associated with different types of leukemias and lymphomas, benzidine with bladder cancer, nickel with lung cancer, chromium compounds with lung cancer, nose and nasal sinus cancer. The greatest occupational exposure to benzene is in industry (leather, electronic device, shoes, sports equipment), while people may come into contact with benzidine through consumer goods (leather products, clothes, toys). The highest concentrations of nickel were measured in the beans, walnuts and grains. Cadmium and cadmium compounds cause lung cancer, and influence the occurrence of renal and prostate cancer. The risk of hepatocellular carcinoma is significantly increased in respondents with high concentrations of urinary metabolites of aflatoxin (aflatoxin N7-gvanine adducts). Lindane isomers are present in dairy products, meat, fish, poultry, garden fruit, oils and lipids, leaf and root vegetables and sugar, and they cause noon-Hodgkin lymphoma. There is a positive correlation between the consumption of aristolochia plants and the occurrence of urothelial carcinoma. There are no screening examinations for the identification of persons who are at great risk of developing malign disease in the next 10 or 20 years. As for the prevention of malign diseases, it is necessary to put an accent on finding the adequate methods for determining the concentrations of urinary metabolites for chemical carcinogens and define their risk values.
Keywords: urinary metabolites, chemical carcinogens, malign diseases